Community Driven Development In Traditional Communities In Papua - Yannice Luma Marnala Sitorus (The Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Abstract. Community-Driven Development is a social planning concept aimed at changing the behaviour and attitude of marginalized communities in other to empower them. This means with their own ability they can collectively solve social and economic problems in their environment. By using various participatory approaches, that are considered most suitable in the postmodern planning era, this development concept is expected to increase the welfare of underprivileged communities. This concept is also applied in the development of traditional communities, especially for customary tradition communities, but has not yet had a significant impact. This study uses existing literature to show the general results of community-driven development in traditional communities, especially traditional communities in Papua. Many development programmes were run by the government using participatory approaches. The study shows that the desired social change is not yet observed for traditional communities in Papua, who have obtained community-driven development programmes for so many years. These communities still have the lowest level of welfare in Indonesia. The social learning that was expected to happen in any community-driven development program with participatory approaches happens very slowly in Papua. Keywords. community empowerment, traditional communities, social changeAbstrak. Pembangunan berbasis pemberdayaan masyarakat sebenarnya merupakan suatu konsep perencanaan sosial yang bertujuan untuk mengubah perilaku dan sikap sosial masyarakat yang termarjinalkan agar dapat menjadi lebih berdaya, yang artinya dengan kemampuannya sendiri secara bersama-sama dapat menyelesaikan masalah-masalah sosial dan ekonomi di lingkungannya. Dengan menggunakan berbagai pendekatan partisipatif, yang dianggap paling sesuai pada era 'postmodern planning' ini, konsep pembangunan tersebut diharapkan dapat meningkatkan kesejahteraan masyarakat yang berada pada level bawah. Konsep ini juga diterapkan dalam pembangunan masyarakat tradisional, khususnya komunitas adat, tetapi belum memberikan dampak yang berarti. Kajian ini menggunakan literatur yang ada untuk menunjukkan bagaimana hasil pembangunan berbasis pemberdayaan masyarakat secara umum pada komunitas adat, khususnya komunitas adat di Papua. Program-program pembangunan tersebut banyak dijalankan oleh pihak pemerintah dengan menggunakan pendekatan-pendekatan partisipatif. Hasil kajian menunjukkan bahwa perubahan sosial yang diinginkan ini belum terlihat pada komunitas adat di Papua yang telah sekian tahun memperoleh program-program pembangunan berbasis masyarakat. Komunitas tersebut masih memiliki tingkat kesejahteraan terendah di Indonesia. Pembelajaran sosial yang diharapkan dapat terjadi dalam setiap program pembangunan berbasis pemberdayaan masyarakat dengan pendekatan partisipatif berjalan sangat lambat di Papua.Kata kunci. pemberdayaan masyarakat, komunitas adat, perubahan sosial